eCM 2017
DOI: 10.22203/ecm.v033a15
|View full text |Cite
|
Sign up to set email alerts
|

The BMP2 variant L51P restores the osteogenic differentiation of human mesenchymal stromal cells in the presence of intervertebral disc cells

Abstract: Spinal fusion is hampered by the presence of remaining intervertebral disc (IVD) tissue and leads to spinal nonunion. While the exact mechanism remains unknown, we hypothesise that factors preventing disc ossification, such as antagonists of the bone morphogenetic proteins (BMP), could be responsible for this process.The objective of this study was to investigate spinal non-union using an in vitro human model with a focus on the BMP signalling components and to identify factors contributing to the incomplete a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…[18][19][20] However, studies on primary human cells are very rare. Tekari et al 7 have shown that osteogenesis of human mesenchymal stem cells cocultured with human IVD cells can be rescued with the addition of L51P. Generally, all stimulations-BMP2 and L51P in CM and OM but also OM only-showed a tendency for ACAN and COL2 upregulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[18][19][20] However, studies on primary human cells are very rare. Tekari et al 7 have shown that osteogenesis of human mesenchymal stem cells cocultured with human IVD cells can be rescued with the addition of L51P. Generally, all stimulations-BMP2 and L51P in CM and OM but also OM only-showed a tendency for ACAN and COL2 upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Recent studies have shown that mesenchymal stromal cells (MSCs) are prevented from undergoing osteogenesis when cocultured with IVD cells. 6,7 Several bone morphogenetic proteins (BMPs) are effective stimulators of osteogenesis. BMP2 and 7, which are U.S. Food and Drug Administration approved, are used in clinics as osteoinductive factors during spinal fusion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For osteogenic differentiation, NP cells were cultured in osteogenic-inducing medium as previously described 28 . After 7-day osteogenic differentiation, ALP activity was evaluated with the ALP staining kit (Biyuntian Biotech Co., Ltd., Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%